A LABORATORY SIMULATION OF FIBROUS VEINS: SOME FIRST OBSERVATIONS - Means W.D.; Li T. (My University, 2001)
Following work by Stephen Taber 80years ago, we describe vein-like arrays of parallel, fibrous crystals that grow evaporatively between pairs of brine-soaked, porous ceramic substrates. Crystals of solute grow antitaxially from fixed sites on the substrate, forcing older parts of the crystals away from the growth site, without benefit of any long-range cracking parallel to the substrate. The nutrients for growth are fed to the growth site advectively or diffusively through the substrate blocks themselves, not along the plane of the vein. We call such crystallization Taber growth and suggest, as Taber did, that it might be an important mechanism for non-evaporative fibrous vein development in nature. The Taber growth model provides a ready explanation for the ability of fibers to track vein opening directions, and tracking is indeed the rule in our samples, though exceptions are also seen. Our results lend support to ideas already in the literature that fibrous veins are not necessarily products of a crack-seal process and that fibrous veins are not necessarily syntectonic. Our observations also raise questions about criteria for recognition of syntaxial fibrous veins and underscore the importance of finding new criteria for recognition of the younging direction along fibers.